2014
DOI: 10.1111/ijag.12090
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Embossing Stage of the Ultrasonic‐Vibration‐Assisted Hot Glass Embossing Process

Abstract: Ultrasonic vibration technology has recently been applied in high‐temperature forming processes, such as hot upsetting and hot glass embossing. Experimental research has delineated the effects of ultrasonic vibration on reducing required forces and improving the formability of materials. The purpose of this study was to construct a finite element model of the embossing stage of the ultrasonic vibration‐assisted hot glass embossing process. Traditional hot embossing experiments in which the embossing speed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Furthermore, Hung et al [6] reported that embossing forces reduced markedly when applying ultrasonic vibration into hot glass embossing process. In addition, some experiments were carried out to study effect of some parameters on force reduction under effect of ultrasonic vibration by using different embossing speeds, changing various embossing temperatures and extending the applying time of ultrasonic vibration [7]. Recently, Nguyen et al [8] have tried to emboss the rectangular pyramid arrays on the glass substrate using ultrasonic vibration assisted-hot embossing process.…”
Section: Fig 3 Ultrasonic Vibration-assisted Hot Glass Embossing Processmentioning
confidence: 99%
“…Furthermore, Hung et al [6] reported that embossing forces reduced markedly when applying ultrasonic vibration into hot glass embossing process. In addition, some experiments were carried out to study effect of some parameters on force reduction under effect of ultrasonic vibration by using different embossing speeds, changing various embossing temperatures and extending the applying time of ultrasonic vibration [7]. Recently, Nguyen et al [8] have tried to emboss the rectangular pyramid arrays on the glass substrate using ultrasonic vibration assisted-hot embossing process.…”
Section: Fig 3 Ultrasonic Vibration-assisted Hot Glass Embossing Processmentioning
confidence: 99%
“…Since the formed contact angles are determined by internal stresses of the glass and glass‐mold interfacial frictions, this difference indicates that the contact mechanical characteristics on glass‐mold interfaces are transformed in UGMP. More likely, the average contact pressure and average frictional force are reduced, which have been demonstrated in Nguyen's and Zhou's experimental results …”
Section: Discussion On Micro‐formabilitymentioning
confidence: 99%
“…It was concluded that the high energy of the ultrasonic vibration would lead to a temperature rise in glass K‐PSK100. Consequently, the molding pressure was dramatically reduced, while the microformability of the glass was significantly improved . On the other hand, Zhou and Xie studied the mechanism of UGMP based on the ultrasonic mechanical effect, and the results showed that the ultrasonic vibration could reduce the contact time between the resin preform and molds, as well as homogenize the stress distribution inside the formed microgrooves.…”
Section: Introductionmentioning
confidence: 99%
“…This model could not only describe the glass behavior under embossing force but also express the effect of ultrasonic vibration. Standard linear solid (SLS) model, one kind of viscoelastic models, which combines a Maxwell model and a spring in series, was proposed for the glass deformation behavior during the embossing stage [8] (as shown in Figure 17). Substituting complex strain and complex stress from Eq.…”
Section: Finite Element Analysis Of Ultrasonic Vibration-assisted Hotmentioning
confidence: 99%